Influence of Dietary Supplementation of Dried Purslane (Portulaca oleracea L.) Powder on Growth Performance and Susceptibility of Chicken Thigh Muscle to Lipid Oxidation During Frozen Storage Conditions - Safari, Hassan; Mohit, Ardeshir; Mohiti-Asli, Maziar (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to examine the effects of dried purslane powder (DPP) supplementation to broiler diet on growth performance and susceptibility of thigh muscle to lipid oxidation during frozen storage at -20Â° C for six months. One hundred sixty one-day-old chicks were allocated in a completely randomizeddesign into four treatments and four replicates with 10 birds in each replication. DPP was included @ 0, 2.5, 5 and 7.5% of the diet in treatments DPP0, DPP2.5, DPP5 and DPP7.5, respectively. The feed intake was more (P